Not Just Luck: Uncovering the Secret Skills and Expertise of Second-hand Shoppers - Frahm, Lea Becker; Laursen, Linda Nhu (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
In this paper, we study second-hand shopping as an expertise that can be practiced. While second-hand markets are rapidly growing, consumers still find it difficult and challenging to purchase second-hand, as the shopping experience is messier, complex and unpredictable. We investigate the process of skill acquisition to understand the skill development of shopping second-hand. Based on 14 interviews, this research illustrates a progression in second-hand shopping behaviors as individuals gain experience. This study categorises second-hand shopping expertise into six levels, highlighting distinct behaviors and strategies. We find: 1) Novices are overwhelmed, lack confidence, and rely entirely on others to assess quality and price. 2) Initiates show a narrow focus on specific products and apply external expertise but struggle to broaden their scope. 3) Apprentices use structured strategies, targeting pre-researched items and avoiding unstructured second-hand environments. 4) Journeymen demonstrate proficiency within selected product categories, researching brands and quality indicators to compare items with nuanced criteria. 5) Experts possess deep but abstract knowledge of product quality and durability, allowing them to identify high-resale potential items without prior research while maintaining frequent, informed engagement with second-hand markets. 6) Masters showcase comprehensive expertise, relying on intuition, ingrained knowledge, and fast-browsing techniques to navigate diverse product categories effortlessly. These findings offer a framework for improving second-hand shopping skills across expertise levels.